The Role of Contextual Learning in Raising the Level of Academic Aspiration among Students of the Department of Art Education - Nadeem Jabr Al-Alaq, Wiam ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
The current research aimed to investigate the role of contextual learning in raising the level of academic aspiration among students of the Department of Art Education. To achieve this, the researcher adopted the experimental method, using a two-group design (experimental and control). The research population consisted of second-year students in the Department of Art Education at the Colleges of Basic Education at Al-Mustansiriyah University and the University of Misan, totaling (220) male and female students. A random sample of (80) students was selected, distributed equally between the experimental group (40) and the control group (40(.To accomplish the objectives of the research, the researcher developed a scale consisting of (24) items, the validity and reliability of which were verified before application to the research sample. The results revealed a statistically significant difference at the level of (0.05) between the mean scores of the experimental and control groups on the post-test of the academic aspiration scale, in favor of the experimental group. In addition, a statistically significant difference was found between the pre-test and post-test scores of the experimental group, also in favor of the post-test. The study concluded that teaching based on contextual learning contributed to raising the level of academic aspiration among students of the Department of Art Education through encouraging their orientation toward study, viewing the future positively, striving for excellence and perseverance, bearing responsibility, and developing self-confidence and satisfaction. Accordingly, the researcher recommended the use of contextual learning in educational programs that enhance academic aspiration, and the organization of seminars and workshops to raise students’ awareness of the importance of academic aspiration and engagement, and their role in developing knowledge and skills. The researcher also suggested conducting further studies on the effect of contextual learning-based programs in art education courses for students of Colleges of Basic Education, as well as exploring the relationship between academic aspiration and mental capacity in these colleges. DOI: https://doi.org/10.54633/2333-024-056-025